Mycovirus in Pseudocercospora griseola, the causal agent of angular leaf spot in common bean - Lima, Swiany Silveira (2010)
Pseudocercospora griseola (Sacc.) Crous & Braun is a widespread fungal phytopathogen that is responsible for angular leaf spot in the common bean (Phaseolus vulgaris L.). A number of fungal phytopathogens have been shown to harbour mycoviruses, and this possibility was investigated in populations of Pseudocercospora griseola. The total nucleic acid extracts of 61 fungal isolates were subjected to agarose gel electrophoresis. Small fragments (800–4800 bp) could be identified in 42 of the samples. The presence of dsRNA in isolate Ig838 was confirmed by treatment of total nucleic acid with DNase, RNase A, and nuclease S1. Transmission electron microscopy revealed the presence of viral-like particles 40 nm in diameter in the mycelia of 2 fungal isolates, namely 29-3 and Ig838. The transmission of dsRNA by means of conidia was 100% for isolate 29-3, but there was loss of 1–6 fragments of dsRNA in monosporic colonies of isolate Ig848. Cycloheximide treatment failed to inhibit the mycovirus in isolate 29-3, but proved efficient in the elimination of the 2.2, 2.0, 1.8, 1.2 and 1.0 kb fragments in 2 colonies of isolate Ig848. The occurrence of a mycovirus in Pseudocercospora griseola was demonstrated for the first time in the present study.